Perovskite Materials Synthesis, Characterisation, Properties, and Applications - Pan, Likun; Zhu, Guang (IntechOpen, 2016)
The book summarizes the current state of the know-how in the field of perovskite materials: synthesis, characterization, properties, and applications. Most chapters include a review on the actual knowledge and cutting-edge research results. Thus, this book is an essential source of reference for scientists with research fields in energy, physics, chemistry and materials. It is also a suitable reading material for graduate students.